Ethnobotany, Chemical Constitution and Biological Activities of Moquilea Genus: A Systematic Review - Delgado-Rodríguez, Fabián Vinicio; Porras-Navarro, Marta; Villalobos-Gätjens, Natalia; Sandí-Flores, Jeniffer; Chaves-Hernández, Valeria (Pharmacognosy Reviews)
Moquilea (Chrysobalanaceae) is a taxon recently separated from previous Licania genus. Several plants from Moquilea genus have been studied for the evaluation of their biological properties and chemical constitution analysis, especially those used as edible material and as a medicinal agent in several countries from tropical zones of America where the plants are endemic. Considering these facts, the present systematic review has the aim to summarize available information about ethnobotany, chemical components and biological effects inves tigated for Moquilea plants. For this purpose, eight data bases (Pubmed, ACS publications, EBSCOhost, ScienceDirect, SciELO, SpringerLink, Tayor and Francis Online and Wiley Online Library) were search and 2116 results corresponding to full-text articles and book chapters were screened using defined inclusion criteria. Finally, information from 45 documents were included in the review. According to compilated information, there are few species with avail able data related to their ethnobotanical applications. However, there is a wide variety of biological activities reported for extracts and isolated components obtained from Moquilea plants, including antioxidant, antimicrobial, cytotoxic and gastroprotective effects. Polyphenols and triterpenes are the major secondary metabolites reported among Moquilea plants.
Keywords: Activities; Ethnobotany; Extracts; Metabolites; Moquilea